The Evaluation of Geotube Behaviors on Muddy Beach: Field Monitoring and Numerical Analysis - Lee, Siew Cheng; Hashim, Roslan; Mo, Kim Hung (Springer Verlag (Germany), 2018)
The use of geotubes is now common in coastline protection due to notable advantages such as erosion prevention, competitive cost and speedy installation procedures. Previous researchers have presented analytical, empirical and numerical approaches for geotube design. However, design approach for geotube which functions as breakwater on deformable muddy foundation and subjected to hydrodynamic loads has not been well reported. Hence, this study evaluates the behavior of geotube breakwaters installed on a deformable muddy foundation based on field measurements and numerical analysis. The field measurements were carried out on quarter-yearly basis to assess the behavior of geotube under hydrodynamic forces. Two-dimensional finite element analysis was performed to simulate the deformation and the displacement of geotube breakwater subjected to hydrodynamic loads, taking into account of deformable foundation condition. The structural stability and structure’s height reduction due to foundation settlement are essential considerations in breakwater design. The agreements between field monitoring and numerical results were promising; therefore, the finite element models can be used to predict the behavior of geotube on those muddy coast areas with similar hydrodynamic and geological conditions.